Processed foods and the consumer : additives, labeling, standards, and nutrition - Packard, Vernal S. (University of Minnesota Press, 1976)
Processed Foods and the Consumer was first published in 1976. Minnesota Archive Editions uses digital technology to make long-unavailable books once again accessible, and are published unaltered from the original University of Minnesota Press editions. In this comprehensive guide, Professor Packard discusses problems and answers questions of paramount importance to the consumer concerning processed foods that are sold in the marketplace. The book is an excellent text for course use in classes in food science or technology, nutrition, dietetics, institutional food management, and related courses. It is also a valuable reference work for those in food industries and regulatory and health agencies, and for the concerned public.